Removable partial denture alloys processed by laser‐sintering technique. Issue 3 (31st May 2017) - Alageel, Omar; Abdallah, Mohamed‐Nur; Alsheghri, Ammar; Song, Jun; Caron, Eric; Tamimi, Faleh
Abstract: Removable partial dentures (RPDs) are traditionally made using a casting technique. New additive manufacturing processes based on laser sintering has been developed for quick fabrication of RPDs metal frameworks at low cost. The objective of this study was to characterize the mechanical, physical, and biocompatibility properties of RPD cobalt–chromium (Co–Cr) alloys produced by two laser‐sintering systems and compare them to those prepared using traditional casting methods. The laser‐sintered Co–Cr alloys were processed by the selective laser‐sintering method (SLS) and the direct metal laser‐sintering (DMLS) method using the Phenix system (L‐1) and EOS system (L‐2), respectively. L‐1 and L‐2 techniques were 8 and 3.5 times more precise than the casting (CC) technique ( p  < 0.05). Co–Cr alloys processed by L‐1 and L‐2 showed higher ( p  < 0.05) hardness (14–19%), yield strength (10–13%), and fatigue resistance (71–72%) compared to CC alloys. This was probably due to their smaller grain size and higher microstructural homogeneity. All Co–Cr alloys exhibited low porosity (2.1–3.3%); however, pore distribution was more homogenous in L‐1 and L‐2 alloys when compared to CC alloys. Both laser‐sintered and cast alloys were biocompatible. In conclusion, laser‐sintered alloys are more precise and present better mechanical and fatigue properties than cast alloys for RPDs. © 2017 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 106B: 1174–1185, 2018.